Napoleon, Alexander I, Franciscus II - Vinkeles, Reinier, 1741-1816 (engraver):::Creator::::::::::::; Kuyper, Jacques, 1761-1808 (artist):::Contributor::::::::::::
Engraved portraits of Napoleon, Francis II (later Francis I) of Austria, and Alexander I.